Effects of the Nordic Hamstring exercise on sprint capacity in male football players: a randomized controlled trial - Ishøi, L.; Hölmich, P.; Aagaard, P.; Thorborg, K.; Bandholm, T.; Serner, A. (Journal of Sports Sciences, 2018)
This assessor-blinded, randomized controlled superiority trial investigated the efficacy of the 10-week Nordic Hamstring exercise (NHE) protocol on sprint performance in football players.